(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
I have composed an educational plan used to improve reading interpretation and writing catharsis of the Bible. Upon studying the theory of the inequity of justice practice within my moral faith, I wanted to express my feelings of the Church through a poem. I felt I owed it to God to provide a positive reflection of my faith to others so they could relate to the Bible and understand my position of faith. Faith is a measurement of time utilized to explicate meaning.